(untitled) (Docentes 2.0 Journal, 2021)
In the last decades of the previous century, a dizzying technological advance emerged in the world. The educational systems were not far from these advances; teaching from virtuality was a new challenge, which caused different projects for this purpose. Teaching performance in pedagogical practice requires a high level of preparation and knowledge on the part of the teacher, which is where the methodological and investigative work is reflected. The objective of this research was to implement a pedagogical model to improve teaching performance with a focus on technological competencies. A descriptive methodology was used for each of the four stages under a mixed approach. Of the 52 professors belonging to the University of Artemisa, 35 selected an intentional non-probabilistic sample. The consultation with specialists was carried out with seven teachers from the Rubén Martínez Villena Higher Pedagogical Institute, 5 of them with more than 25 years of experience at the higher level. The results achieved served as a starting point to characterize teaching performance, focusing on technological competencies, and measuring indicators. Subsequently, it provided teachers with the construction of their learning resources related to their identified competencies, technical context, and subject; this made the teaching process significant.